High involvement of human resource management practices, organizational citizenship behavior and job satisfaction in Royal Malaysia Customs - Sew, Lai Yan (2018)
The purpose of this study was to investigate the influences of high involvement human resource management (HRM) practices and organizational citizenship behavior (OCB) on job satisfaction. High involvement of HRM practices was divided into five dimensions namely recognition practices, empowerment practices, competence development practices, fair reward practices and information sharing practices. The relationship between these five dimensions to OCB and the relationship between OCB to job satisfaction of employee in Royal Malaysia Customs Department (RMCD) Perak was explored in this study. 250 questionnaires were distributed to the employees in RMCD Perak and in return, 200 questionnaires were collected. Regression analysis was used to examine the relationship between those variables. Results indicated that the positive significant relationship was found between empowerment practices, competence development practices, fair reward practices and information sharing practices to OCB as well as the positive significant relationship between OCB and job satisfaction. However, results showed that there was no significant relationship between recognition practices and OCB. The study aims to contribute to organization that intend to use OCB as an instrument to increase the level of employee satisfaction as well as to enhance the human resources management, organizational citizenship and job satisfaction.